Structure, Conduct and Performance of Onion Market in Southern Ghana - Camillus Abawiera Wongnaa; Richard Kwasi Bannor; Raymond K Dziwornu; Joel Atta Ennin; Emmanuel Assibey Osei; Courage Adzikah; Arthur Charles (Universitas Sebelas Maret, 2022)
The local onion market in Ghana is dominated by ‘on the spot’ market relationships with little or no coordination of chains to improve quality and performance. This study examines the market structure, conduct and their influence on the performance of the onion market in the southern part of Ghana, using data from 180 actors, comprising 80 farmers, 40 wholesalers and 60 retailers. Descriptive statistics, Gini coefficient, Lorenz curve, Herfindahl-Hirschman index and Garett ranking were the methods of analysis used. The results showed that traders were operating in an oligopolistic market with Gini coefficients of 0.62 and 0.56 for wholesalers and retailers, respectively. The findings also revealed that farmers (69%) were more open to contracts than wholesalers (20%) and retailers (11%). Moreover, onion production proved to be costly for farmers as they had a negative return of 1.55% on their investment while wholesalers and retailers made positive returns of 29.85% and 31.1%, respectively. Finally, high production cost, high marketing cost and unavailability of storage structures were ranked as the most pressing constraints to farmers, wholesalers and retailers, respectively. It is recommended that the government, donor support agencies for agriculture and local NGOs come to the aid of farmers by providing them with fixed assets at a subsidized price. This will relieve the farmers from heavy losses which threaten the future food security of the country.